2006
DOI: 10.1161/01.atv.0000242013.29441.81
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Smooth Muscle Proliferation by Urea-Based Alkanoic Acids via Peroxisome Proliferator-Activated Receptor α–Dependent Repression of Cyclin D1

Abstract: Objective-Proliferation of smooth muscle cells is implicated in cardiovascular complications. Previously, a urea-based soluble epoxide hydrolase inhibitor was shown to attenuate smooth muscle cell proliferation. We examined the possibility that urea-based alkanoic acids activate the nuclear receptor peroxisome proliferator-activated receptor ␣ (PPAR␣) and the role of PPAR␣ in smooth muscle cell proliferation. Methods and Results-Alkanoic acids transactivated PPAR␣, induced binding of PPAR␣ to its response elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
3
19
1
Order By: Relevance
“…sEH inhibitors initially were developed as antihypertensive agents (11), but recent data indicate that they also prevent cardiac hypertrophy (43), decrease vascular smooth muscle proliferation (44), improve renal hemodynamics (3), and decrease hypertensive renal damage (10,45). This is consistent with the finding that angiotensin II up-regulates sEH through a transcriptional mechanism, thereby reducing EET availability (46).…”
Section: Seh Inhibitionsupporting
confidence: 55%
“…sEH inhibitors initially were developed as antihypertensive agents (11), but recent data indicate that they also prevent cardiac hypertrophy (43), decrease vascular smooth muscle proliferation (44), improve renal hemodynamics (3), and decrease hypertensive renal damage (10,45). This is consistent with the finding that angiotensin II up-regulates sEH through a transcriptional mechanism, thereby reducing EET availability (46).…”
Section: Seh Inhibitionsupporting
confidence: 55%
“…These results were confirmed with porcine SMCs (Zahradka et al 2006), as well as human aortic and coronary artery SMCs (Gizard et al 2005;Ng et al 2006). The cellular mechanisms for inhibition of DNA synthesis were linked to cdk2 activation (Zahradka et al 2006), cyclin D1 expression (Ng et al 2006) and p16 INK4a (Gizard et al 2005). Given the critical role of the retinoblastoma protein (Rb) in cell cycle progression through the G1/S interface (Andres 2004), it is reasonable to suggest that Wy14,643 affects a common event required for Rb activation that is mediated by PPARα.…”
Section: Direct Actions Of Wy14643 On Vascular Tissuesupporting
confidence: 63%
“…It was observed that Wy14,643 inhibited SMC proliferation in response to both angiotensin II and plateletderived growth factor (PDGF), respectively. These results were confirmed with porcine SMCs (Zahradka et al 2006), as well as human aortic and coronary artery SMCs (Gizard et al 2005;Ng et al 2006). The cellular mechanisms for inhibition of DNA synthesis were linked to cdk2 activation (Zahradka et al 2006), cyclin D1 expression (Ng et al 2006) and p16 INK4a (Gizard et al 2005).…”
Section: Direct Actions Of Wy14643 On Vascular Tissuesupporting
confidence: 55%
“…Unfortunately, inhibition of sEH by ureabased and chalcone oxide sEH inhibitors was not possible in these studies since these inhibitors also activated PPARs (V. Y. Ng and D. L. Kroetz, unpublished data;Ng et al, 2006). Further studies would be required to adequately address the relative contribution of EETs and DHETs in the observed activation of PPAR.…”
Section: Analysis Of P450 Eicosanoid Levels In Hepg2 Cellsmentioning
confidence: 99%